2023
DOI: 10.1002/rmv.2436
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of hepatitis C core antigen assay to identify active infections: A systematic review and meta‐analysis

Abstract: Hepatitis C virus (HCV) core antigen (HCVcAg) assay is an alternative for diagnosing HCV infection in a single step. This meta‐analysis aimed to evaluate the Abbott ARCHITECT HCV Ag assay's diagnostic performance (validity and utility) for diagnosing active hepatitis C. PubMed, EMBASE, Scopus, Web of Science, and Cochrane Library were searched until 10 January 2023. The protocol was registered at the prospective international register of systematic reviews (PROSPERO: CRD42022337191). Abbott ARCHITECT HCV Ag as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…Sensitivity (98.0%, CI: 95.4%-99.3%) and specificity (98.6% CI: 95.0%-99.8%) for HCVcAg in our study with a cut-off of ≥3 fmol/L, is consistent with other studies. 6 Another study from Pakistan, reported a lower sensitivity and specificity of 96.8% and 91.8% (95%, CI: 83%-97%) 7 at ≥3 fmol/L. While they reported the higher HCVcAg sensitivity at a threshold of ≥10 fmol/L (99.1%, CI: 95-100%).…”
Section: Discussionmentioning
confidence: 94%
“…Sensitivity (98.0%, CI: 95.4%-99.3%) and specificity (98.6% CI: 95.0%-99.8%) for HCVcAg in our study with a cut-off of ≥3 fmol/L, is consistent with other studies. 6 Another study from Pakistan, reported a lower sensitivity and specificity of 96.8% and 91.8% (95%, CI: 83%-97%) 7 at ≥3 fmol/L. While they reported the higher HCVcAg sensitivity at a threshold of ≥10 fmol/L (99.1%, CI: 95-100%).…”
Section: Discussionmentioning
confidence: 94%
“…HCVcAg correlates well with HCV RNA levels ≥10 000 IU/mL and, thus, can detect viremia in the vast majority of persons with active HCV infection. A recent metanalysis of 46 studies using HCVcAg reported the assay to have high specificity and sensitivity for active HCV infection but suboptimal positive predictive value in low prevalence settings [ 16 ]. Nonetheless, this test may be a valuable addition to the rapid diagnostic armamentarium, especially in high-prevalence settings where nucleic acid testing is less feasible or unavailable [ 15 ].…”
Section: Remaining Issues With Hcv Diagnostic Down-classificationmentioning
confidence: 99%